Analysis of Public Diplomacy Through Teacher Exchanges in the Framework of Quality Improvement in ASEAN - Alfianda, Jaka Tiwana; Suparno, Suparno (Ridwan Institute, 2025)
The SEA Teacher program, initiated by SEAMEO, is a regional effort aimed at enhancing educational cooperation within the ASEAN region through student-teacher exchanges among member countries. The program was launched to address the growing demand for higher quality education, promote regional identity, and foster cross-cultural understanding amid globalization. This study aims to analyze the SEA Teacher program as a form of public diplomacy, emphasizing the people-to-people approach, which strengthens relations among ASEAN citizens through educational and cultural exchanges. Employing a juridical-normative methodology with both conceptual and legislative approaches, the study examines how laws and policies support the program's implementation and explores the concepts of public diplomacy and soft power within the education framework. The study's findings reveal that the SEA Teacher program plays a crucial role in educational diplomacy, enhancing the image of participating countries, fostering communication between nations, and reinforcing regional solidarity through the direct experiences of participants in diverse cultural settings. Furthermore, the program demonstrates that educational exchange serves as a strategic tool of public diplomacy, enriching academic experiences while fostering social trust and regional integration in ASEAN. The legal and policy implications include the need for harmonized regulations regarding academic recognition, the protection of participants, and strengthened institutional commitments to exchange programs as part of foreign policy initiatives focused on education and culture.